German nominal compounds and their equivalents in Old Prussian catechisms of the 16th century - Jarmalavičius, Dalius (Baltistica, 2019)
This paper deals with German nominal compounds in three Old Prussian catechisms of the 16th century published in Early New High German (Germ. Frühneuhochdeutsch). The analysis focuses on the prevailing word-formation types of nominal compounds in German and their translation equivalents in Old Prussian. The present analysis includes 65 words in German. With regard to the fact that the introductions of catechisms had not been translated into Old Prussian, only 46 nominal compounds recorded in the bilingual text of catechisms were selected for the analysis of equivalents of German compounds according to the word-formation patterns in Old Prussian. The results of word-formation analysis of catechisms are compared with another bilingual source – the Elbing Vocabulary of the 15th century. According to the research findings, the majority of the German compounds recorded in catechisms are compounds with two noun constituents. Except for a few examples, which belong to verbal governing compounds, the majority of the examples found are determinative nouns. About two-thirds (61%) of the German nominal compounds are translated into Old Prussian as word phrases and, less frequently, as simplex words.
Keywords: German; Old Prussian; catechisms; Elbing Vocabulary; word formation; compounding; nominal compounds